Alcoholic Liver Cirrhosis in Young Female: Diagnostic and Therapeutic Challenge - Syifa Mustika; Nina Nur Arifah (The Indonesian Society for Digestive Endoscopy, 2017)
Alcoholic liver cirrhosis is a disease due to excessive alcohol consumption that manifest as fatty liver, alcoholic hepatitis, and chronic hepatitis with fibrosis or liver cirrhosis. Alcohol consumption as much as 60-80 g per day for 20 years or more in male, or 20 g/day (approximately 25 mL/day) in female significantly increases the risk of hepatitis and fibrosis as much as 7-47%. The aim of this case report was to explore the diagnostic and therapeutic challenge of alcoholic liver disease in young aged female. A female, 24 years old, came with complaints of bloody vomiting, blacktarry stool, abdominal distention and history of alcohol consumption (canned beer 5%, equal to 56-70 g/day) for 9 years. Physical examination revealed anaemic conjunctiva (Hb 2.9 g/dL), ascites, hepatosplenomegaly, and bilateral legs oedema. Laboratory examinations showed thrombocytopenia (125000/uL) and hypalbuminaemia (2.65 gr/dL). AST and ALP were increased with the value of 175 U/L and 456 U/L, respectively. Albumin-globulin ratio was 0.93 g/dL with serum ascites albumin-gradient was 2.20 g/dL (ascites fluid albumin level was 0.45 gr/dL and serum albumin level was 2.65 gr/dL). Abdominal USG revealed hepatomegaly with coarse heterogenic ecoparenchyma, portal vein dilatation, and splenomegaly. Diagnosis of alcoholic liver cirrhosis was made based on clinical, laboratory, and radiologic findings, while biopsy result did not confirm the pathology. Patients condition improved with education of stop alcohol consumption and was given supportive therapy.